On the construction of an asymptotic solution of a perturbed Bretherton equation - Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider the application of the asymptotic method of nonlinear mechanics to the construction of the first and second approximations of a solution of the Bremerton equation.